PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI DI KANTOR SEKRETARIAT KOMISI PENYIARAN INDONESIA DAERAH (KPID) PROVINSI KEPULAUAN RIAU - Riduward Siahaan; Tibrani Tibrani; Ade Parlaungan Nasution (EQUILIBIRIA, 2014)
The research was conducted at the Secretariat of KPID Riau Islands Province. The purpose of this study was to determine the effect of leadership style and cultural work on employee performance, either separately (partial) or jointly (simultaneously). In this study, the authors used a sample of 26 employees were taken on the whole of the total population (employees). While the types of data used are primary data and secondary data. Sources of primary data obtained from questionnaires, while secondary data obtained from the Secretariat of Administration documents KPID Riau Islands Province and related literature and research to support this. Data Collection Techniques conducted by interviews and questionnaires. Data were analyzed by descriptive statistics, which are used to give a picture of the object under study through the sample data associated with the relevant theories and quantitative techniques in accordance with the Likert scale and to the results of the test using SPSS (Statistical Product and Service Solutions) version 20.              From the research, the authors conclude that partial Leadership Style (X1) and a significant positive effect on employee performance (Y), with test results of 0.657 or 65.7%, and Cultural Work (X2) and a significant positive effect on employee performance (Y), with test results of 0.526 or 56.6. Simultaneous testing leadership style and cultural work positive and significant effect (strong) on employee performance with a sledge to at 0.828 or 82.8%, as for the rest of 0.172 or 17.2% influenced by variables or other factors. Keywords: Leadership Style, Cultural Work and Employee Performance.